2012
DOI: 10.1136/archdischild-2012-302633
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic abnormalities and body composition of HIV-infected children on Lopinavir or Nevirapine-based antiretroviral therapy

Abstract: Background Few studies have assessed metabolic and body composition alterations in young perinatally HIV-infected African children on antiretroviral therapy (ART). We compared metabolic profiles and regional fat of children on a combination of ritonavir-boosted lopinavir (lopinavir/ritonavir), lamivudine, and stavudine to those switched to nevirapine, lamivudine, and stavudine. Methods This study evaluated metabolic and body composition outcomes in 156 HIV-infected children completing a randomized trial that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 42 publications
7
81
3
1
Order By: Relevance
“…For consistency with prior publications on shorter-term outcomes, we used this protocol-defined composite outcome. While the primary focus of this trial was HIV-related outcomes, studies have shown unfavorable alterations in lipid profiles and body composition among infants on LPV/r [27,28]. Longitudinal data on such outcomes are needed as, with current treatment recommendations, the duration of LPV/rbased ART exposure will only increase for perinatally infected children.…”
Section: Discussionmentioning
confidence: 99%
“…For consistency with prior publications on shorter-term outcomes, we used this protocol-defined composite outcome. While the primary focus of this trial was HIV-related outcomes, studies have shown unfavorable alterations in lipid profiles and body composition among infants on LPV/r [27,28]. Longitudinal data on such outcomes are needed as, with current treatment recommendations, the duration of LPV/rbased ART exposure will only increase for perinatally infected children.…”
Section: Discussionmentioning
confidence: 99%
“…PIs are associated with dyslipidaemia and lipodystrophy 103, 111, 112, 113. However, once‐daily PIs, such as ATV/r and DRV/r, in adults tend to cause fewer lipid abnormalities 114, 115, 116.…”
Section: Drug Toxicities and Interactionsmentioning
confidence: 99%
“…The Nevirapine Resistance Study (NEVEREST), a randomized trial of switching NVP‐exposed infants from suppressive LPV/r‐ to NVP‐based ART (after at least 3 months of VL < 400 copies/ml), showed that this strategy can be successful in infants without evidence of transmitted NVP resistance on conventional testing 64, 197. Children switched to NVP had less long‐term dyslipidaemia and subcutaneous fat loss 112. Furthermore, the recently reported results of the NEVEREST‐3 study 198 indicate that switching children fully suppressed on LPV/r to EFV‐based ART is a safe and effective strategy in the context of prophylactic NVP exposure.…”
Section: When To Switch Resistance Testing and Second And Subsequentmentioning
confidence: 99%
“…PIs adversely affect lipid parameters, and data from adult studies suggest that alternative once-daily boosted PIs may have more favourable lipid profiles compared with LPV/r [2,3]. While a switch from PIs to nonnucleoside reverse transcriptase inhibitors (NNRTIs) has been shown to improve lipid profiles in paediatric cohorts [4], data are lacking regarding the optimal PI for children who have previously failed NNRTI-based regimens.A retrospective case note audit of a single-centre cohort of paediatric patients switching from suppressive LPV/r-to ritonavir-boosted atazanavir (ATV/r)-or darunavir (DRV/r)-based ART was performed. Retrospective data were collected at two time-points; 2-7 and 11-18 months post-switch.…”
mentioning
confidence: 99%